Autochthonous probiotic bacteria modulate intestinal microbiota of Pirarucu, Arapaima gigas. Issue 6 (29th July 2019) - do Vale Pereira, Gabriella; Pereira, Scheila Anelise; Soares, Arno; Mouriño, Jose Luiz Pedreira; Merrifield, Daniel
Abstract: This study aimed to investigate the ability of two probiotic strains ( Lactococcus lactis subsp. lactis and Enterococcus faecium ) to colonize Arapaima gigas intestines and their competence in modulating gut microbiota, morphology, and immunological status. A total of 135 A. gigas (58.86 ± 10.25 g) were divided into three treatments: (a) fish fed a diet containing L. lactis subsp. lactis at 1 × 10 8 CFU −1, (b) fish fed a diet containing E. faecium at 1 × 10 8 CFU −1, and (c) fish fed a diet nonsupplemented with probiotic. After 21 days, 12 fish per treatment were sampled. Blood and posterior intestine were sampled for further analysis. High‐throughput sequencing results demonstrated that the relative abundance of Cetobacterium genus was high in all treatments. The number of thrombocytes increased in both groups fed the probiotic, and eosinophils were higher in fish fed E. faecium . Serum antimicrobial activity of fish fed L. lactis subsp. lactis was higher when compared with the other two treatments. In conclusion, both strains could populate the intestinal mucosa of A. gigas and could be used as probiotics in pirarucu production as they can influence hematoimmunological parameters and decrease the abundance of pathogenic bacteria in the gut of pirarucu within 21 days of feeding.